2020
DOI: 10.1021/acs.macromol.0c01518
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Photoinitiators with Near-Resonance Enhanced Two-Photon Absorption Cross-Section: Toward High-Resolution Photoresist with Improved Sensitivity

Abstract: We take advantage of the near-resonant enhancement of the third-order nonlinear response to engineer a two-photon polymerization photoinitiator with optimized efficiency in regard to literature benchmarks. We study in detail its linear and resonant third-order nonlinear optical properties, with particular focus on photoinduced radical generation. Careful choice of peripheral substituents enables its direct solubilization into a mixture of commercial multifunctional acrylic monomers, resulting in a homogeneous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 101 publications
0
31
0
1
Order By: Relevance
“…All reagents were used without further purification. Three resins were used in this study based on the use of a photoinitiator (PI) previously reported by our team [32,33]: PR_organic (DPPHA/DDA/V-Shape, weight ratio: 79.2/19.8/1, includes ca. 600 ppm MEHQ as stabilizer/polymerization inhibitor), PR_hybrid (PI-free Ormocomp/V-Shape, weight ratio: 99.5/0.5, stabilizer free) and stabilized PR_hybrid (PI-free Ormocomp/V-Shape, weight ratio: 99.5/0.5 + 700 ppm MEHQ).…”
Section: Microfabricationmentioning
confidence: 99%
“…All reagents were used without further purification. Three resins were used in this study based on the use of a photoinitiator (PI) previously reported by our team [32,33]: PR_organic (DPPHA/DDA/V-Shape, weight ratio: 79.2/19.8/1, includes ca. 600 ppm MEHQ as stabilizer/polymerization inhibitor), PR_hybrid (PI-free Ormocomp/V-Shape, weight ratio: 99.5/0.5, stabilizer free) and stabilized PR_hybrid (PI-free Ormocomp/V-Shape, weight ratio: 99.5/0.5 + 700 ppm MEHQ).…”
Section: Microfabricationmentioning
confidence: 99%
“…Another limiting factor for achieving high printing rates is the sensitivity of the photoresist. Much work has been done to develop two-photon photoinitiators with improved photoinitiating capabilities [48][49][50][51] .…”
Section: Continuous Layer-by-layer Projection Two-photon Lithography Systemmentioning
confidence: 99%
“…The TPA cross section σ 2 is often represented as “ δ ” and has units of m 4 s molecule −1 photon −1 , typically expressed in units of “GM” (1 GM = 1 × 10 −58 m 4 s molecule −1 photon −1 ). Augmenting polarizability of PAGs by judicious incorporation of donor/accepter moieties can increase δ up to two orders of magnitude [ 28 , 38 , 39 , 40 ] compared to that of common UV initiators [ 41 ]. Increasing δ enhances the sensitivity of the resin and enables fabrication at lower powers.…”
Section: Su-8 As a Materials System For Mplmentioning
confidence: 99%